The effects of heat treatment on the AISI 316L stainless steel overlay with respect to its PREN - Khow, Stephen Junjie. (2009)
The effects of post-welding heat treatments on grade 316L austenitic stainless steel overlay and how much it differs from its PREN value are studied. PREN values are commonly used commercially to deduce the corrosion resistance of stainless steels but their effectiveness are in doubt. Samples of both 316L overlay and regular 316L alloy are heat treated at from 600 to 1100۫C for 4 hours. SEM/EDX analyses are performed on the 316L overlay samples and found that carbon contents of all samples had increased. Further ferrite number and hardness measurements also determined the temperature range which delta ferrite thermally decomposed most significantly into secondary phases such as sigma phase. The trends in ferrite number and hardness only happen to the 316L overlay samples. The presence of sigma phase was reflected by an increase in the amount of weight loss per surface area. Delta ferrite decomposition was slowed down when samples are heated beyond 850۫c and this was also reflected by a smaller weight loss. This was due to the diffusion of carbon which suppresses the formation of sigma phase through the formation of chromium carbides. Pitting factor was presumably to determine the extent of pitting corrosion but was later found out that it strongly depend on the dimensions of the samples. The effect of heat treatments on the corrosion resistance of all the 316L overlay samples was not reflected by the PREN value.